2021
DOI: 10.3390/electronics10060666
|View full text |Cite
|
Sign up to set email alerts
|

EREBOTS: Privacy-Compliant Agent-Based Platform for Multi-Scenario Personalized Health-Assistant Chatbots

Abstract: Context. Asynchronous messaging is increasingly used to support human–machine interactions, generally implemented through chatbots. Such virtual entities assist the users in activities of different kinds (e.g., work, leisure, and health-related) and are becoming ingrained into humans’ habits due to factors including (i) the availability of mobile devices such as smartphones and tablets, (ii) the increasingly engaging nature of chatbot interactions, (iii) the release of dedicated APIs from messaging platforms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 51 publications
0
19
0
2
Order By: Relevance
“…e early development of chatbot was mostly dominated by a single domain. It has been observed that more research has been directed towards open domain [45][46][47][48][49] and multidomain [50][51][52] in recent years. Single-domain chatbots are limited to accomplishing specific tasks, while multidomain or open domain chatbots can better meet the needs of smart assistants and even further provide people's companionship or social applications.…”
Section: Discussionmentioning
confidence: 99%
“…e early development of chatbot was mostly dominated by a single domain. It has been observed that more research has been directed towards open domain [45][46][47][48][49] and multidomain [50][51][52] in recent years. Single-domain chatbots are limited to accomplishing specific tasks, while multidomain or open domain chatbots can better meet the needs of smart assistants and even further provide people's companionship or social applications.…”
Section: Discussionmentioning
confidence: 99%
“…While prior work has examined design implications [2,40,50,69] and technological implementations [12] for conversational personalization systems, how to design personalization of such a system has been relatively less explored. As personalization of information is a key feature of such conversational systems, compared to other systems like a reporting or logging tool, a deeper understanding in design issues arising from personalization is necessary.…”
Section: Dialogue-based Interactive Systems For Support-seeking Of Se...mentioning
confidence: 99%
“…Figure 1 shows the EREBOTS platform [6] comprises four main components: Database management, Communication Server, Multi-Agent System back-end for the doctor agents, and Multi-Agent System back-end and front-end for the patient agents.…”
Section: Architecture Of the Agent-based Chatbot Platformmentioning
confidence: 99%
“…In this paper, we introduce a cohort and trajectory analysis (CTA) approach for the EREBOTS agent-based personalized chatbot system [6]. The CTA enables EREBOTS to support patients through treatment adjustment, and provides a dedicated interface for clinicians to fine-tune the chatbot behaviors.…”
Section: Introductionmentioning
confidence: 99%